Predicting The Role of Perceived Destination Attractiveness to Visit Intention of Tourists to Davao Ecotourism Sites - Jimenez, Florence Kristina; Rodriguez, Dyann Kate; Modesto, Angela Sheralyn; Sumague, Jonathan (La Ricerca, 2023)
This study aims to predict the role of perceived destination attractiveness in to visit intention of tourists to Davao ecotourism sites. A total of 672 respondents were surveyed through online platforms. Most of these respondents are from Davao City, female and completed a bachelor's degree, aged 18 to 25 years old, and are considered millennial tourists. Five-factor loadings emerged that describe the measures of ecotourism attractiveness: service quality, Communication facilities, aesthetics, Local culture, and recreation. Further, research findings show that respondents are very much willing to visit Davao City as an Ecotourism destination. Moreover, the results of the Spearman Rank Order Correlation show that perceived factors of ecotourism destination attractiveness have a statistically significant correlation with visit intentions. It suggests that the more attractive the destination is, the higher the likelihood that tourists will visit Davao City's ecotourism sites. These findings challenge the local tourism government to improve the ecotourism destinations of Davao City to invite more influx of tourists. Findings on the differences in the perception of respondents on destination attractiveness as well as on visit intention may also provide practical implications to tourism planners and marketers, particularly in creating varied packages that would suit the needs of different market segments. Lastly, the study results contribute to the literature focusing on Davao ecotourist behaviors.